English Language Assessment Practices in Batam Secondary Schools: Teachers’ Strategies, Constraints, and Pedagogical Negotiations - Oey, Anton; Mariati, Mariati; Tandiani, Alexandria (International Journal of Language Teaching and Education, 2026)
This study examines English language assessment practices in Batam secondary schools by focusing on how teachers balance pedagogical goals, institutional requirements, and classroom constraints. The study employed a qualitative descriptive design using interview interview records from English teachers representing several school contexts in Batam, including junior high school, senior high school, vocational school, and independent school settings. The data were analyzed thematically across recurrent domains such as oral and written assessment, formative and diagnostic assessment, feedback practices, project and quiz use, summative examination structure, grading systems, assessment media, and classroom challenges. The findings indicate that teachers generally value balanced, authentic, and student-centered assessment, yet written assessment remains more dominant because it is more practical in large classes and easier to align with formal school reporting. Oral assessment is still considered indispensable because it reveals confidence, fluency, pronunciation, and spontaneous language use that written work often cannot capture. The study also shows that formative assessment is commonly implemented through quizzes, games, classroom interaction, worksheets, projects, and short performance tasks, while summative assessment tends to prioritize reading, grammar, vocabulary, and writing. Digital tools such as Google Forms, Quizizz, Wordwall, ZEPP, Exambro, and school-based systems are used selectively, but teachers continue to rely on paper-based records and direct classroom observation to ensure fairness and authenticity. The paper argues that assessment in Batam secondary schools reflects an ongoing negotiation between authenticity and manageability, and that future improvement should strengthen performance-based assessment, clearer rubrics, and practical institutional support for teachers.